DEVELOPMENT OF FORWARD GRAIN PROCUREMENT BY WHOLESALE TRADE IN THE CONTEXT OF EUROPEAN INTEGRATION - KUPALOVA, Halyna; MAGOMEDOVA, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Іn the modern context of global market transformation and increasing financial risks, one of the most dynamic and in-demand instruments for wholesale grain procurement is forward contracts, which enable producers to lock in the price and volume of products in advance, thereby reducing dependence on market fluctuations and creating prerequisites for stable production development. Their flexibility and multifunctionality ensure not only predictable cash flows but also increased trust from banking institutions and investors, opening access to credit and additional financing. The article emphasizes the risk management mechanism, particularly price, currency, and financial risks, which are an integral part of forward agreements. It is determined that the use of such contracts allows agricultural producers to effectively plan costs and revenues, shape development strategies, and minimize risks associated with market instability. A classification of forward contracts by type, underlying asset, and contracting parties is proposed, which makes it possible to better understand their features and applications. Special attention is paid to innovative financial instruments, including agrarian receipts and agrarian notes. The latter have significant advantages for attracting financing and making settlements, as they combine flexibility, transparency, and the potential for digitalization of operations. The prospects for the development of forward grain purchases using agrarian notes are highlighted, which foresee improved access to financial resources, reduction of price and credit risks, optimization of logistics processes, and increased participation of private and institutional investors. The development of forward instruments and digital financial solutions forms the basis for establishing market standards, strengthening the competitiveness of the agricultural business, and ensuring the stability of Ukraine’s agri-food sector in the context of European integration.